2015
DOI: 10.1016/j.cmet.2015.09.002
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Cardiac Fibroblast Growth Factor Receptor 4 Causes Left Ventricular Hypertrophy

Abstract: Summary Chronic kidney disease (CKD) is a worldwide public health threat that increases risk of death due to cardiovascular complications, including left ventricular hypertrophy (LVH). Novel therapeutic targets are needed to design treatments to alleviate the cardiovascular burden of CKD. Previously, we demonstrated that circulating concentrations of fibroblast growth factor (FGF) 23 rise progressively in CKD and induce LVH through an unknown FGF receptor (FGFR)-dependent mechanism. Here, we report that FGF23 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
509
3
3

Year Published

2016
2016
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 457 publications
(550 citation statements)
references
References 42 publications
17
509
3
3
Order By: Relevance
“…In experimental models of mice, Faul et al [22] demonstrated that the FGF23-induced cardiac hypertrophy was abrogated by a phospholipase Cγ inhibitor (U73122) and a calcineurin inhibitor (cyclosporine A), but not by a MAP kinase inhibitor (PD98059), a PI3 kinase inhibitor (wartmannin), or an Akt inhibitor (A6730). Furthermore, pan FGF receptor blockade by PD173074 reduced LV mass and the cardiac expression of genes associated with LV hypertrophy [123], and the receptor involved was identified as FGF receptor 4 [124]. These findings lend support to the premise that FGF23-induced cardiac hypertrophy is mediated by the FGF receptor 4/PLCγ/calcineurin pathway.…”
Section: Fgf23 and Cardiac Hypertrophysupporting
confidence: 54%
“…In experimental models of mice, Faul et al [22] demonstrated that the FGF23-induced cardiac hypertrophy was abrogated by a phospholipase Cγ inhibitor (U73122) and a calcineurin inhibitor (cyclosporine A), but not by a MAP kinase inhibitor (PD98059), a PI3 kinase inhibitor (wartmannin), or an Akt inhibitor (A6730). Furthermore, pan FGF receptor blockade by PD173074 reduced LV mass and the cardiac expression of genes associated with LV hypertrophy [123], and the receptor involved was identified as FGF receptor 4 [124]. These findings lend support to the premise that FGF23-induced cardiac hypertrophy is mediated by the FGF receptor 4/PLCγ/calcineurin pathway.…”
Section: Fgf23 and Cardiac Hypertrophysupporting
confidence: 54%
“…41 The incubation time was 1 hour protected from light. After three washing steps, the sections were labeled by Hoechst diluted 1:1,000 in PBS.…”
Section: Histology and Immunohistochemistrymentioning
confidence: 99%
“…Thus disease states with α-Klotho deficiency may not involve global FGF-23 resistance, but rather they may in fact promote a switch of the FGF-23-induced signaling towards different cellular responses and outcomes in cells which express FGFRs, but not α-Klotho. 56 Previously FGF-23 functions on major organs, directly or indirectly, were considered only when α-Klotho was co-expressed along with FGFRs in the target tissue, 42 but with new studies that have been conducted exploring different mechanisms of action of FGF-23, researchers need to reassess the role FGF-23 plays in the organs and how that is achieved. There is clearly a delicate balance between FGF-23's α-Klotho dependent actions on the FGFRs and its α-Klotho independent actions on FGFR's throughout the body that need to be considered simultaneously and further studied.…”
Section: Klotho-dependent and Klotho-independent Func-tions Of Fgf-23mentioning
confidence: 99%
“…56,65 Activation of this FGFR-4/calcineurin/NFAT pathway has been shown to be enough to cause cardiac hypertrophy in mice while FGFR-4 blockade, even with high serum FGF-23 levels, attenuates cardiac hypertrophy in rats with CKD. 56 In another study FGF-23 has been shown to induce cardiomyocyte hypertrophy via PLC-γ signaling, upstream of calcineurin/NFAT, independent of Klotho. 43 These studies bring to light questions regarding α-Klotho independent functions of FGF-23 in the heart that must be further investigated.…”
Section: Heartmentioning
confidence: 99%